2013
DOI: 10.2105/ajph.2013.301487
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of the US Beer Institute’s Self-Regulation Code Governing the Content of Beer Advertising

Abstract: The alcohol industry's current self-regulatory framework is ineffective at preventing content violations but could be improved by the use of new rating procedures designed to better detect content code violations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Table summarizes 19 studies conducted in 19 countries where advertising content was evaluated in terms of code violations . All studies reported evidence of code violations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table summarizes 19 studies conducted in 19 countries where advertising content was evaluated in terms of code violations . All studies reported evidence of code violations.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies used pre‐selected advertisements that were thought to contain code violations and reported violation rates of 100% . The remaining 12 studies used either a random sample of advertisements or a total survey approach . Among these studies, code violation rates for television and magazine advertisements ranged from 12.3 to 86% and 0 to 52% , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Finally, across five studies, a peanl of expert reviewers who assessed the content of televised alcohol ads identified numerous advertising elements that would boost youth appeal, many of which were in violation of the industry’s self-regulatory advertising codes. 2024 Findings from these qualitative studies are troubling, as research has shown that the models and situations depicted in alcohol advertisements positively influence youth expectations about how they will feel when they drink. 18 …”
Section: Introductionmentioning
confidence: 99%
“…The most common form of alcohol marketing regulation worldwide is alcohol industry self-regulation 3 ; however, numerous studies from multiple countries have shown this form of regulation to be ineffective either in protecting young people from disproportionate exposure to alcohol marketing 129,130 or in restricting objectionable advertising content 131,132 .…”
Section: Discussionmentioning
confidence: 99%